Capital Flows in the Euro Area and TARGET2 Balances - Nikolay Hristov; Oliver Hülsewig; Timo Wollmershäuser (Center for Economic Studies and ifo Institute (CESifo), 2018)
We estimate a panel VAR model for the euro area to quantitatively asses the contribution of the TARGET2 system to the propagation of different types of structural economic shocks as well as to the historical evolution of aggregate economic activity in euro area member countries. Our results suggest that TARGET2 has significantly affected the transmission of capital ow shocks while leaving the macroeconomic responses to other aggregate shocks virtually unaltered. Furthermore, on basis of counterfactual analyses, we find that TARGET2 has contributed substantially to avoid deeper recessions in distressed periphery member countries like Spain, Italy, Ireland and Portugal, while to a smaller degree depressing aggregate economic activity in core member states, such as Germany, the Netherlands and Finland.
Keywords: E42; F32; F41; F45; 330; euro area; TARGET2 balances; capital inflow shocks; panel vector autoregressive model